Strategi Komunikasi Podcaster Detik Sumsel Dalam Meningkatkan Pengetahuan Masyarakat Palembang Terhadap Budaya - Amelia Putri; Fifi Hasmawati; Jufrizal (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This thesis is entitled Detik Sumsel Podcaster's Communication Strategy in Increasing the Palembang Community's Knowledge of Culture. This research was conducted to find out how podcasters' communication strategies increase Palembang society's knowledge of culture. This research focuses on podcasts produced by detik sumsel. Detik Sumsel itself is one of the news media offices in the city of Palembang. Detik Sumsel has a podcast program which is broadcast several times a week on the YouTube channel. The Detik Sumsel Podcast also has several themes presented, but in this research the focus is on the cultural theme which aims to increase the knowledge of the Palembang community regarding culture. This study used qualitative research methods. This research is also a field study, which means primary and secondary data were obtained directly from the South Sumatra Second office. Furthermore, when the data is collected, the data is analyzed using qualitative methods and in the end a conclusion or result from the research can be drawn. The results of this research are that Podcast Detik Sumsel's communication strategy in increasing public knowledge of culture can be said to be good but not yet fully optimal based on the 4 stages of communication strategy.